2006
DOI: 10.1002/dc.20519
|View full text |Cite
|
Sign up to set email alerts
|

Primary relapse of acute lymphoblastic leukemia in a cervical smear: A case report

Abstract: Uterine cervix and corpus are rarely the initial site of relapse in leukemia or lymphoma. We report herein a case of uterine cervical relapse with B-cell acute lymphoblastic leukemia (ALL). The patient, a 60-yr-old woman, had a history of ALL that had been in remission for 2 yr after chemotherapy. She presented with a chief complaint of genital bleeding. In a routine cervico-vaginal Papanicolau smear, abundant atypical lymphoid cells with round-to-oval nuclei, scant cytoplasm, and high nuclear to cytoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In previously reported cases, vaginal lymphoma resulted in ill-defined thickening or induration of the vaginal wall [5, 7]. In our previous report of a case of uterine cervical acute lymphoblastic leukemia (ALL) extended into the vagina, the vaginal wall was macroscopically thickened [8], but in the present case, the vaginal wall was not hard or thickened.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In previously reported cases, vaginal lymphoma resulted in ill-defined thickening or induration of the vaginal wall [5, 7]. In our previous report of a case of uterine cervical acute lymphoblastic leukemia (ALL) extended into the vagina, the vaginal wall was macroscopically thickened [8], but in the present case, the vaginal wall was not hard or thickened.…”
Section: Discussionmentioning
confidence: 50%
“…Several authors have reported lymphoid neoplasms such as lymphoma and leukemia manifesting in gynecological organs [3,4,5,6,7,8,9,10], but the total number of such cases remains small. In autopsy studies of patients with NHL, the uterus was found to be involved in approximately 0.5% of cases and the vagina in 2% [4].…”
Section: Discussionmentioning
confidence: 99%
“…Most hematological malignancies may primarily or secondarily involve the genital tract: in our case lymphoblastic [15] or myeloid [16] leukemia could have been excluded based on the cell size and nucleo/cytoplasmic fetures, while high grade non-Hodgkin lymphoma [17] and anaplastic myeloma [18] could have been the only possible differential due to the nucleolar prominence and large cell size. Some nucleo-cytoplasmic features of the cell population in our case, however, would have strongly dictated against these two entities: the presence of peripheral ring-like cytoplasmic condensations, of irregular cytoplasmic borders evoking hyperplastic microvilli and the extremely lobulated and convoluted shape of the nuclear membrane: this latter seemed excessive even for a high grade lymphoma of convoluted cell type.…”
Section: Differential Diagnosis and Discussionmentioning
confidence: 99%
“…Amongst genitourinary organs, testis is the most common site of involvement in ALL [8]. Cases of ovarian and cervix involvement in ALL are limited to case reports only [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%